RNF43 truncations trap CK1 to drive niche‐independent self‐renewal in cancer. (10th August 2020) - Spit, Maureen; Fenderico, Nicola; Jordens, Ingrid; Radaszkiewicz, Tomasz; Lindeboom, Rik GH; Bugter, Jeroen M; Cristobal, Alba; Ootes, Lars; van Osch, Max; Janssen, Eline; Boonekamp, Kim E; Hanakova, Katerina; et al.
Abstract: Wnt/β‐catenin signaling is a primary pathway for stem cell maintenance during tissue renewal and a frequent target for mutations in cancer. Impaired Wnt receptor endocytosis due to loss of the ubiquitin ligase RNF43 gives rise to Wnt‐hypersensitive tumors that are susceptible to anti‐Wnt‐based therapy. Contrary to this paradigm, we identify a class of RNF43 truncating cancer mutations that induce β‐catenin‐mediated transcription, despite exhibiting retained Wnt receptor downregulation. These mutations interfere with a ubiquitin‐independent suppressor role of the RNF43 cytosolic tail that involves Casein kinase 1 (CK1) binding and phosphorylation. Mechanistically, truncated RNF43 variants trap CK1 at the plasma membrane, thereby preventing β‐catenin turnover and propelling ligand‐independent target gene transcription. Gene editing of human colon stem cells shows that RNF43 truncations cooperate with p53 loss to drive a niche‐independent program for self‐renewal and proliferation. Moreover, these RNF43 variants confer decreased sensitivity to anti‐Wnt‐based therapy. Our data demonstrate the relevance of studying patient‐derived mutations for understanding disease mechanisms and improved applications of precision medicine. Synopsis: The Wnt pathway‐antagonising tumor suppressor RNF43 is frequently lost in human malignancies. Identification of a distinct class of patient‐derived RNF43 truncating mutations that drive Wnt receptor/β‐catenin target expression in a ligand‐independent manner may impact on current cancer treatment schemes. Expression of C‐terminally‐truncated RNF43 increases β‐catenin‐mediated transcription in the absence of Wnt ligands. Truncated RNF43 retains destruction complex components CK1 and AXIN at the plasma membrane. CK1α‐mediated phosphorylation of the cytosolic tail of truncated RNF43 activates intracellular Wnt signaling. Oncogenic RNF43 induces TP53‐dependent epithelial growth arrest in human colon organoids, and decreases sensitivity to anti‐Wnt-based therapy. Abstract : C‐terminal shortening of RNF43 promotes Wnt/β‐catenin by decreasing destruction complex activity without effects on its ubiquitin ligase activity.